2009
DOI: 10.1007/s00464-009-0478-3
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic resection of large pedunculated colonic polyps and risk of postpolypectomy bleeding with adrenaline injection versus endoloop and hemoclip: a prospective, randomized study

Abstract: Combined endoscopic techniques seem to be more effective in preventing postpolypectomy bleeding in large pedunculated colonic polyps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
1
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(67 citation statements)
references
References 28 publications
0
60
1
4
Order By: Relevance
“…16 With regard to adrenaline injection compared to endoloop and hemoclip a prospective study, 3 has shown that there are no differences between both techniques in post-polypectomy bleeding prophylaxis, although the combination of both procedures appears to be more efficient. 17 Several studies compared detachable snare versus epinephrine injection, reporting no difference in delayed post-polypectomy and similar efficacy either by placing endoloops or by injecting epinephrine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 With regard to adrenaline injection compared to endoloop and hemoclip a prospective study, 3 has shown that there are no differences between both techniques in post-polypectomy bleeding prophylaxis, although the combination of both procedures appears to be more efficient. 17 Several studies compared detachable snare versus epinephrine injection, reporting no difference in delayed post-polypectomy and similar efficacy either by placing endoloops or by injecting epinephrine.…”
Section: Discussionmentioning
confidence: 99%
“…3 Therefore, based on an anticipated decrease of at least 12% in the rate of adverse bleeding events between the group treated using hemoclips and the group treated using conventional methods, there was an alpha error of 0.05 and a statistical power of 80% (beta error of 0.2) with a patient inclusion rate of 1:1. The number of polyps required is 146 per group.…”
Section: Statistical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…L'association la plus utilisée dans ce cas est l'injection du pied du polype avec 2 à 5 ml de sérum salé isotonique additionné d'adrénaline (1/10 000), associée à la mise en place d'une anse d'hémostase (Polyloop) [11]. La coupe peut être augmentée à 200 W si le pied du polype est large (> 1 cm).…”
Section: Indications Et Techniques Endoscopiques Polypectomieunclassified
“…Prophylactic measures like adrenaline injection [22][23][24][25][26][27] or mechanical haemostasis [23][24][25] to prevent PPH have been studied, but have not been universally adopted, or recommended in guidelines. One meta-analysis examined the use of prophylactic haemostatic measures in preventing PPH, 28 but included smaller polyps (<10 mm) which are less likely to bleed.…”
Section: Introductionmentioning
confidence: 99%